2008
DOI: 10.1212/01.wnl.0000297551.27191.70
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine in migraine headache

Abstract: Overall, oxcarbazepine was safe and well tolerated; however, oxcarbazepine did not show efficacy in the prophylactic treatment of migraine headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…3336 Notably, even within class, some drugs are effective (e.g., antiepileptics such as valproate and topiramate) 13,37,38 while others (e.g., oxcarbazepine) are not. 39 Moreover, many of these treatments are associated with troublesome side effects, including sedation, difficulty in thinking, and weight gain, and are not well tolerated in many patients. Because many patients do not respond to current prophylactic medications, a strong medical need for discovery of new therapeutics exists.…”
Section: Chronic Migraine and Medication Overuse Headachementioning
confidence: 99%
“…3336 Notably, even within class, some drugs are effective (e.g., antiepileptics such as valproate and topiramate) 13,37,38 while others (e.g., oxcarbazepine) are not. 39 Moreover, many of these treatments are associated with troublesome side effects, including sedation, difficulty in thinking, and weight gain, and are not well tolerated in many patients. Because many patients do not respond to current prophylactic medications, a strong medical need for discovery of new therapeutics exists.…”
Section: Chronic Migraine and Medication Overuse Headachementioning
confidence: 99%
“…Oxcarbazepine was not effective for migraine prophylaxis in a placebo-controlled trial. 28 Lamotrigine was less efficacious for migraine than topiramate in a small double-blind placebo-controlled trial and only marginally better than placebo, 29 confirming the general clinical impression that lamotrigine has low efficacy for migraine.…”
Section: Unique Patient and Antiepileptic Drug Characteristicsmentioning
confidence: 84%
“…Carrazana found that the evidence supporting the use of OXC for trigeminal neuralgia is strong [9,10]. The use of OXC for other indications such as painful diabetic neuropathy, post-herpetic neuralgia, painful paroxysmal symptoms in multiple sclerosis, tremor, and migraine has already been investigated with a poor-moderate evidence level [5,[11][12][13][14]. In this study, the use of OXC in trigeminal neuralgia is categorized as offlabel use because the distribution license in Indonesia does not include an indication for OXC in trigeminal neuralgia.…”
Section: Discussionmentioning
confidence: 99%